Galería de palabras : la variedad de la ecfrasis - Artigas Albarelli, Irene (Pública Crítica ;, 2013)
Essays exploring relationship between visual and literary arts. Revives and expands on age-old concept of ekphrasis, referring to rhetorical exercise offering dramatic description of work of art. Pairs and compares writers with artists of many cultures and time periods: William Carlos Williams and Seamus Heaney with Brueghel; Margaret Atwood with Manet; Joseph Cornell with Octavio Paz and Elizabeth Bishop; and others.